2015
DOI: 10.1037/fam0000085
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-origin parents’ work conditions and adolescents’ adjustment.

Abstract: Mexican-origin parents’ work experiences are a distal extra-familial context for adolescents’ adjustment. This two-wave multi-informant study examined the prospective mechanisms linking parents’ work conditions (i.e., self-direction, work pressure, workplace discrimination) to adolescents’ adjustment (i.e., educational expectations, depressive symptoms, risky behavior) across the transition to high school drawing on work socialization and spillover models. We examined the indirect effects of parental work cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 49 publications
(89 reference statements)
4
16
0
Order By: Relevance
“…In conclusion, the maternal parenting typology developed through this study provided useful information about cultural specificities in socialization practices in Portugal and Spain. The results presented here support the growing body of empirical research, which outlines how parenting practices depend on cultural backgrounds [1,[18][19][20][21]31,65,66]. The description of the parental socialization styles characteristic of each country, due to their cultural influence, has implications for interventions.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion, the maternal parenting typology developed through this study provided useful information about cultural specificities in socialization practices in Portugal and Spain. The results presented here support the growing body of empirical research, which outlines how parenting practices depend on cultural backgrounds [1,[18][19][20][21]31,65,66]. The description of the parental socialization styles characteristic of each country, due to their cultural influence, has implications for interventions.…”
Section: Discussionsupporting
confidence: 71%
“…Community-based organizations must educate Latino residents about their rights, ensure that these rights are not violated, and counteract rumors that can have a chilling effect on Latino families’ use of public services. Given robust negative implications of parent psychological distress for adolescents [21,22], alongside the large portion of Latino adolescents who are U.S. citizens, pathways to citizenship for Latino parents are critical in order to mitigate long-term, collateral consequences for numerous Americans.…”
Section: Discussionmentioning
confidence: 99%
“…The costs and burdens of psychological distress extend far beyond an affected individual. Parents’ psychological distress is especially important; adolescents whose parents are depressed and/or anxious face heightened risk of poor social functioning [21], academic failure [22], and mental health problems [21].…”
mentioning
confidence: 99%
“…Parents' experiences of racial discrimination at work predicted poorer adolescent outcomes through different mechanisms for mothers and fathers, showing the importance of assessing work culture in relation to race and gender. In an interesting twist, findings for fathers revealed that workplace pressure was related to increased connections to their child's life, perhaps reflecting Mexican fathers' values of serving as authority figures and role models to their children and “determination to make sure their children are on the right track” (Wheeler, Updegraff, & Crouter, , p. 454). Similar to research with White samples, Wheeler, Updegraff, and Crouter () found parents' positive job experiences were related to the parent–child relationship quality through the mediator of parents' well‐being.…”
Section: Paid Work and Familiesmentioning
confidence: 99%